Foundations for a theoretical methodological conception of the specialized training of the school principal - Valiente Sandó, Pedro; González Ramírez, Jorge; del Toro Prada, José Javier (Avances en Supervisión Educativa, 2014)
The new requirements stated to the school today demand the specialization and professionalization of the school principal, processes where his specialized training has a decisive role. A proposal of foundations is presented for the creation of a theoretical-methodological conception of such training establishing: its singular nature, the need of its development in stages systemically related; its realization through the combination of ways of the postgraduate education, the methodological work and the scientific-pedagogical activity; and its significance as a process where two other sub processes are distinguished: the first one pedagogical, which claims for the application of special didactical-methodological criteria and recommendations, and another managerial, which execution means a group of specific implications.